RESISTENSI PLASMA NUTFAH IRRDB 1981 TERHADAP PENYAKIT GUGUR DAUN Corynespora - Alchemi Putri Juliantika Kusdiana; Fetrina Oktavia (Widyariset, 2014)
Leaf fall disease caused by Corynespora casiicola can damage the rubber resulting in considerable economic losses. The opportunities to get rubber plant genetic resources that are resistant to leaf fall disease Corynespora casiicola have been made   by testing the resistance of some germplasm IRRDB 1981. Testing the resistances of some germplasm is to produce genetic resources that are resistant to leaf fall diseases and used as parents in the crossing. Testing was done by using immersion leaves method in a solution of toxin C. casiicola. Resistance testing of 28 genotypes germplasm IRRDB 1981 showed various resistance responses. The results indicated that there were five genotypes that had moderate resistant which were PN 323, PN 333, PN 448, PN 494, and PN 593, and one genotype PN 235 showed highly resistant. The six genotypes needed to be tested in the field to determine their interaction with the environment and then used as cross parents to obtain resistant parentage to C. casiicola leaf fall disease.